The historical truth of Sacred Scripture. Reflection based on new document of Pontifical Biblical Commission - Marcin Majewski (Ruch Biblijny i Liturgiczny, 2015)
The new document of the Pontifical Biblical Commission „The Inspiration and Truth of Sacred Scripture” elaborates on the truth in the Bible, also in the context of historical problems that emerge form biblical text. The consensus of modern historians and archaeologists is moving towards separating biblical history and history as a science. In this article I present contemporary discussion on this issue, then I ask, how the document of Pontifical Biblical Commission treats this issue. At the end I suggest directions for further work of biblical scholars.